Globule–stretch transition of a self-attracting chain in the repulsive active particle bath. Issue 8 (8th February 2019) - Xia, Yi-qi; Tian, Wen-de; Chen, Kang; Ma, Yu-qiang
Abstract : The globule(G)–stretch(S) and stretch–globule transitions of a self-attracting chain induced by active particles. Abstract : Folding and unfolding of a chain structure are often manipulated in experiments by tuning the pH, temperature, single-molecule forces or shear fields. Here, we carry out Brownian dynamics simulations to explore the behavior of a single self-attracting chain in a suspension of self-propelling particles (SPPs). As the propelling force increases, the globule–stretch (G–S) transition of the chain occurs due to the enhanced disturbance from the SPPs. Two distinct mechanisms of the transition in the limits of low and high rotational diffusion rates of SPPs have been observed: shear-induced stretching at a low rate and collision-induced melting at a high rate. The G–S and S–G (stretch–globule) curves form a hysteresis loop at the low rate, while they merge at the high rate. Besides, we find that two competing effects result in a non-monotonic dependence of the G–S transition on SPP density at the low rate. Our results suggest an alternative approach to manipulating the folding and unfolding of (bio)polymers by utilizing active agents.